Recent Advances in the Development of Environmentally Benign Treatments to Control Root-Knot Nematodes - Forghani, Fereidoun; Hajihassani, Abolfazl (Frontiers in Plant Science, 2020)
Meloidogyne spp. (root-knot nematodes; RKN) are sedentary endoparasites with wide range of plant hosts. RKN negatively affect almost every crop in the world. Current management practices, though effective to some extent, are not enough to completely control the RKN. Application of certain chemicals is also being further limited in recent years due to increasing regulations and restrictions. Therefore, it is crucial to develop additional control strategies through the application of environmentally benign methods. Due to the importance of this topic, there has been much research performed around the world leading to useful outcomes and interesting findings capable of helping agriculture. Hence, it is important to have dependable resources gathering the data produced to facilitate future research. This review discusses the recent findings on the application of environmentally benign treatments to control RKN between 2015 and April 2020. A variety of biological control strategies, natural compounds, soil amendments and other emerging strategies have been included, among which, many showed promising results in RKN control in vitro and/or in vivo. The impact of biologically-based strategies on parasitic and beneficial nematodes continues to be an area of active research and new information on their efficacy will become available in the years to come. In this review, some of the mechanisms involved have been discussed and suggestions were given on maximizing the outcome of the future efforts.